Culture and Sociology in Marxist Theory - Abbas, Boushra (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research discusses the notion of culture and its relationship to sociology in the Marxist theory. It touches upon a group of problems which are of epistemological and methodological importance within the Marxist theory. The research also surveys the current definition of culture within the culturally related societal and scientific circles. This notion is also examined in the traditional Marxist definitions and their more modern counterparts. Moreover, the association between culture and history is touched upon through the Marxist contexts that consider culture as an essential part of the process of history, and more especially of historical work. The later aspect has actually witnessed a vitality of notion when associated with history. That is, work means, in particular, the productive work. It does not only mean the level of goods production, but also that of cultural production too. Within such a context, the research tackles the concept of culture, and it also reaches a concept which it labels as historicized culture or culture of history. As a last point, the meanings of culture and civilization in Marxist philosophy are also stated. Demarcating what is ideological and what is cultural is then explained in a manner where no mixing between the notion of Marxist ideology and that of civilization would take place. Moreover, extreme consideration is paid on our part to reveal modern theories within Marxism itself for the sake of avoiding an unhistoricized mixing of what is civilized and what is ideological in the first place; even if this demarcation is epistemological more than being ontological.